Kelp holdfast microclimates buffer invertebrate inhabitants from extreme temperatures - Frances Perry; Grant A. Duffy; Miles D. Lamare; Ceridwen I. Fraser (Marine Environmental Research, 2024)

Observing change in pelagic animals as sampling methods shift: the case of Antarctic krill - Simeon L. Hill; Angus Atkinson; Javier A. Arata; Anna Belcher; Susan Bengtson Nash; Kim S. Bernard; Alison Cleary; John A. Conroy; Ryan Driscoll; Sophie Fielding; Hauke Flores; Jaume Forcada; et al. (Frontiers in Marine Science, 2024)
Understanding and managing the response of marine ecosystems to human pressures including climate change requires reliable large-scale and multi-decadal information on the state of key populations. These populations include the pelagic animals that support ecosystem services including carbon export and fisheries. The use of research vessels to collect information using scientific nets and acoustics is being replaced with technologies such as autonomous moorings, gliders, and meta-genetics. Paradoxically, these newer methods sample pelagic populations at ever-smaller spatial scales, and ecological change might go undetected in the time needed to build up large-scale, long time series. These global-scale issues are epitomised by Antarctic krill ( Euphausia superba ), which is concentrated in rapidly warming areas, exports substantial quantities of carbon and supports an expanding fishery, but opinion is divided on how resilient their stocks are to climatic change. Based on a workshop of 137 krill experts we identify the challenges of observing climate change impacts with shifting sampling methods and suggest three tractable solutions. These are to: improve overlap and calibration of new with traditional methods; improve communication to harmonise, link and scale up the capacity of new but localised sampling programs; and expand opportunities from other research platforms and data sources, including the fishing industry. Contrasting evidence for both change and stability in krill stocks illustrates how the risks of false negative and false positive diagnoses of change are related to the temporal and spatial scale of sampling. Given the uncertainty about how krill are responding to rapid warming we recommend a shift towards a fishery management approach that prioritises monitoring of stock status and can adapt to variability and change.

Stepping stones towards Antarctica: Switch to southern spawning grounds explains an abrupt range shift in krill - Angus Atkinson; Simeon L. Hill; Christian S. Reiss; Evgeny A. Pakhomov; Gregory Beaugrand; Geraint A. Tarling; Guang Yang; Deborah K. Steinberg; Katrin Schmidt; Martin Edwards; Emilce Rombolá; Frances A. Perry (Global Change Biology, 2022)
Poleward range shifts are a global‐scale response to warming, but these vary greatly among taxa and are hard to predict for individual species, localized regions or over shorter (years to decadal) timescales. Moving poleward might be easier in the Arctic than in the Southern Ocean, where evidence for range shifts is sparse and contradictory. Here, we compiled a database of larval Antarctic krill, Euphausia superba and, together with an adult database, it showed how their range shift is out of step with the pace of warming. During a 70‐year period of rapid warming (1920s–1990s), distribution centres of both larvae and adults in the SW Atlantic sector remained fixed, despite warming by 0.5–1.0°C and losing sea ice. This was followed by a hiatus in surface warming and ice loss, yet during this period the distributions of krill life stages shifted greatly, by ~1000 km, to the south‐west. Understanding the mechanism of such step changes is essential, since they herald system reorganizations that are hard to predict with current modelling approaches. We propose that the abrupt shift was driven by climatic controls acting on localized recruitment hotspots, superimposed on thermal niche conservatism. During the warming hiatus, the Southern Annular Mode index continued to become increasingly positive and, likely through reduced feeding success for larvae, this led to a precipitous decline in recruitment from the main reproduction hotspot along the southern Scotia Arc. This cut replenishment to the northern portion of the krill stock, as evidenced by declining density and swarm frequency. Concomitantly, a new, southern reproduction area developed after the 1990s, reinforcing the range shift despite the lack of surface warming. New spawning hotspots may provide the stepping stones needed for range shifts into polar regions, so planning of climate‐ready marine protected areas should include these key areas of future habitat.

Temperature–Induced Hatch Failure and Nauplii Malformation in Antarctic Krill - Frances A. Perry; So Kawaguchi; Angus Atkinson; Sévrine F. Sailley; Geraint A. Tarling; Daniel J. Mayor; Cathy H. Lucas; R. King; A. Cooper (Frontiers in Marine Science, 2020)